The impact of social interactions on organisational performance in sports: A case study of Ambon City's sports organisations - Fenanlampir, Albertus; Budiatin, Yasmu; Hasbullah, Bahmid (UIR Press, 2023)
Studying the impact of social interactions on sports organisations’ performance in Ambon City remains a relatively unexplored area. This research aims to address this gap by investigating the influence of social interactions among administrators, coaches, and athletes on sports organisations' performance. Additionally, it explores the disparity in performance levels between individual and team sports. The study focused on sport administrators in Ambon City affiliated with the Indonesian National Sports Committee (KONI). Fifteen participants were selected through purposive sampling, comprising administrators, coaches, and athletes from various sports branches, including athletics, taekwondo, boxing, water skiing, and football. Findings suggest that sports organisation management in Ambon City has not yet achieved optimal levels of effectiveness and facilitation, affecting the dynamics of group sports in particular. Team sports display a higher dependency on teamwork and board roles, notably the coach’s role. Despite suboptimal management, athletes retain the freedom to determine their paths to success or achievement. However, an imbalance exists between expectations and obligations in social relationships, except for the coach-athlete relationship. In summary, this study sheds light on the role of social interactions in sports organisations’ performance and highlights the differences between individual and team sports in Ambon City. These insights may serve as a foundation for more effective management strategies to enhance sports organisations’ performance in the future.